Arctic Climate Issues 2011: Changes in Arctic Snow, Water, Ice and Permafrost. SWIPA 2011 Overview Report. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2012)
AMAPs 2011 assessment of the Arctic Cryosphere (the SWIPA assessment) updates information presented in the 2004/5 Arctic Climate Impact Assessment. Canada, Denmark, Norway, Nordic Council of Ministers